Pengaruh Kualitas Pelayanan, Kepercayaan, dan Harga terhadap Kepuasan Pelanggan pada Jasa Layanan Pesan Antar Produk Online Grabfood di Bekasi - Kurniawati Mulyanti (Fakultas Ekonomi Universitas Islam 45, 2024)
This research aims to determine the influence of service quality, trust, and price on customer satisfaction with the GrabFood online product delivery service among students at the 45 Islamic University of Bekasi. The method used was quantitative descriptive with probability sampling techniques, involving 150 respondents who had used the GrabFood service more than twice. Data analysis was carried out using multiple linear regression with the help of the SPSS program. The research results show that service quality, trust, and price have a positive and significant influence on customer satisfaction. Simultaneously, these three variables also contribute greatly to explaining the level of customer satisfaction, although there are still other factors outside this research that also influence it. These findings confirm that improving service quality, customer trust, and competitive pricing can increase user satisfaction with delivery services.